Pengaruh Pemberian Air Rebusan Bawang Putih (Allium Sativum) Terhadap pH Saliva Buatan yang Diinduksi Streptococcus mutans Secara In Vitro - Firani, Novi Khila; Subandi, regian_fahmi02 (E-Prodenta Journal of Dentistry, 2025)
Saliva or spit is a complex fluid that plays an important role produced by the salivary glands to maintain the balance of the ecosystem in the mouth. The acidity in saliva is influenced by Streptococcus mutans because it can accelerate the process of creating an acidic environment in saliva. The infusion of garlic (Allium Sativum) contains allicin, ajoene, flavonoids, and essential oils that can inhibit the growth of the bacteria Streptococcus mutans. The aim of this research is to determine the effect of garlic (Allium Sativum) decoction on the pH of saliva artificially induced by Streptococcus mutans in vitro. This research employs a True Experimental Design, specifically the Pretest and Posttest Control Group Design. The concentrations used in this study are 25%, 50%, and 100%. The results indicate a difference in the pH levels of artificial saliva that has been induced by Streptococcus mutans and treated with garlic decoction in vitro. The data analysis utilized correlation and regression tests, showing an influence of 73.3% of garlic decoction on the pH of artificial saliva. Independent T-test showed a significant difference between the same groups with different observation times, namely in treatment 1 day 2 with treatment 1 day 3 of 0.013 (p<0.05). Based on this research, it can be concluded that garlic boiled water has an effect and relationship in increasing the pH of saliva artificially induced by Streptococcus mutans in vitro.